Open up the Doors Music in the Modern Church. - Evans, Mark, 1973- (London : Equinox Pub., 2006)
Represents an attempt to provide objective criteria and analytical frameworks by which the quality and function of contemporary congregational music can be assessed. This book also considers how well modern music is serving the modern church, and also how effectively it is operating as a musical form in the secular culture that surrounds it.
Cover; Contents; Acknowledgements; Introduction; 1. Contextualising Contemporary Congregational Music; 2. 'Nothing New Under the Sun': Learning from History; 3. Ending the Corporate Worship Wars; 4. Resistance or Accommodation: The 'World' of Quality; 5. The Rise and Rise of Pentecostal Music: History, Hillsong and Star Texts; 6. Theomusicological Frameworks for Congregational Song Analysis; 7. Corporate Worship GetsPersonal; 8. Conclusion: 'When the Music Fades'; Appendix: Song Classification and Analysis; Notes; Bibliography; Index to Bible References; Subject Index.
Description based on print version record.
Keywords: Contemporary Christian music; Contemporary Christian music -- History and criticism; Music in churches; MUSIC / Instruction & Study / Theory; RELIGION / Christian Rituals & Practice / Worship & Liturgy; RELIGION / Institutions & Organizations; Electronic books